Adaptive multiphoton endomicroscopy through a dynamically deformed multicore optical fiber using proximal detection - Warren,SC; Kim,Y; Stone,JM; Mitchell,C; Knight,JC; Neil,MAA; Paterson,C; French,PMW; Dunsby,CW (Optics Express, 2016)
This paper demonstrates multiphoton excited fluorescenceimaging through a polarisation maintaining multicore fiber (PM-MCF)while the fiber is dynamically deformed using all-proximal detection.Single-shot proximal measurement of the relative optical path lengths of allthe cores of the PM-MCF in double pass is achieved using a Mach-Zehnderinterferometer read out by a scientific CMOS camera operating at 416 Hz.A non-linear least squares fitting procedure is then employed to determinethe deformation-induced lateral shift of the excitation spot at the distal tip ofthe PM-MCF. An experimental validation of this approach is presented thatcompares the proximally measured deformation-induced lateral shift infocal spot position to an independent distally measured ground truth. Theproximal measurement of deformation-induced shift in focal spot position isapplied to correct for deformation-induced shifts in focal spot positionduring raster-scanning multiphoton excited fluorescence imaging.